Antibiotic Resistance in Bangladesh: The Silent Epidemic (Community Based Medical Journal, 2026)
Bangladesh is experiencing a silent but genuinely antibiotic resistance epidemic. Since it makes many infections more difficult or impossible to treat, it is becoming a bigger hazard to public health. In this review, the present status of antibiotic resistance in Bangladesh is discussed. It draws attention to the fact that germs that were formerly easily treated are now developing resistance to numerous conventional antibiotics. Staphylococcus aureus, Salmonella species, Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumoniae are significant resistant bacteria in Bangladesh. These bacteria can be found in the environment, in communities, in hospitals, and in animals. The abuse and overuse of antibiotics is one of the primary causes of antibiotic resistance in Bangladesh. Antibiotics are frequently taken without a doctor's prescription. Pharmacies sell a lot of medications without a prescription. In order to accelerate animal growth and avoid sickness, farmers provide antibiotics to livestock and poultry. This contributes to the spread of resistance in people and animals. In hospitals, the issue is exacerbated by inadequate infection control, poor cleanliness, and a shortage of clean water. The absence of effective surveillance mechanisms is another significant problem. Many labs and hospitals are unable to accurately identify resistant microorganisms. Programs for antibiotic stewardship are extremely rare. There is also extremely little public knowledge on the proper usage of antibiotics. There are policies, but they are not adequately implemented. According to this review, Bangladesh's antibiotic resistance requires immediate intervention. Better legislation, enhanced monitoring, public awareness campaigns, and appropriate use of antibiotics in humans and animals are all urgently needed. Connecting the health of humans, animals, and the environment requires a ‘One Health’ strategy. If nothing is done right now, antibiotic resistance will keep growing and might eventually make minor diseases fatal. To combat this silent epidemic, strong collaboration between the health sectors, stringent enforcement of policies, and ongoing research are essential.  CBMJ 2026 January: vol. 15 no. 01 P: 253-259